Feasibility of high‐intensity interval training in patients with left ventricular assist devices: a pilot study. (17th November 2020) - Alvarez Villela, Miguel; Chinnadurai, Thiru; Salkey, Kalil; Furlani, Andrea; Yanamandala, Mounica; Vukelic, Sasha; Sims, Daniel B.; Shin, Jooyoung J.; Saeed, Omar; Jorde, Ulrich P.; Patel, Snehal R.
Abstract: Aims: Patients with left ventricular assist device (LVAD) suffer from persistent exercise limitation despite improvement of their heart failure syndrome. Exercise training (ET) programmes to improve aerobic capacity have shown modest efficacy. High‐intensity interval training (HIIT), as an alternative to moderate continuous training, has not been systematically tested in this population. We examine the feasibility of a short, personalized HIIT programme in patients with LVAD and describe its effects on aerobic capacity and left ventricular remodelling. Methods and results: Patients on durable LVAD support were prospectively enrolled in a 15‐session, 5 week HIIT programme. Turndown echocardiogram, Kansas City Cardiomyopathy Questionnaire, and cardiopulmonary exercise test were performed before and after HIIT. Training workloads for each subject were based on pretraining peak cardiopulmonary exercise test work rate (W). Percentage of prescribed training workload completed and adverse events were recorded for each subject. Fifteen subjects were enrolled [10 men, age = 51 (29–71) years, HeartMate II = 12, HeartMate 3 = 3, and time on LVAD = 18 (3–64) months]. Twelve completed post‐training testing. HIIT was well tolerated, and 90% (inter‐quartile range: 78, 99%) of the prescribed workload (W) was completed with no major adverse events. Improvements were seen in aV̇O2 at ventilatory threshold [7.1 (6.5, 9.1) to 8.5 (7.7, 9.3) mL/kg/min, P = 0.04], work rate at ventilatory threshold [44 (14, 54) to 55 (21, 66) W, P = 0.05], and left ventricular end‐diastolic volume [168 (144, 216) to 159 (124, 212) mL, n = 7, P = 0.02]. HIIT had no effect on maximal oxygen consumption (V̇O2peak ) or Kansas City Cardiomyopathy Questionnaire score. Conclusions: Cardiopulmonary exercise test‐guided HIIT is feasible and can improve submaximal aerobic capacity in stable patients with chronic LVAD support. Further studies are needed on its effects on the myocardium and its potential role in cardiac rehabilitation programmes.